ANALISIS PENGESAHAN PERDAMAIAN (HOMOLOGASI) TERHADAP PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) ATAS ISI PERJANJIAN PERDAMAIAN YANG MENGALAMI PERUBAHAN (STUDI PUTUSAN: PUTUSAN MAHKAMAH AGUNG NOMOR: 718K/PDT.SUS-PAILIT/2019) - Feiby Annisa; Mia Hadiati (Jurnal Hukum Adigama, 2021)
Reconciliation in the PKPU process is basically the same as an agreement in general, but the peace in the PKPU process is more specific because its enforcement requires legal approval from the court, this is contained in Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. Peace that has received approval from the court is in the form of homologation, resulting in peace becoming a court product, namely in the form of a decision that has permanent legal force. In fact, the homologation decision can still be changed to the contents of the Peace Agreement without a decision from the Commercial Court Judge and the case taken in the Supreme Court Decision Number 718K / Pdt.Sus-Pailit / 2019. The author examines the ratification of peace (Homologation) on the postponement of debt payment obligations (PKPU) on the contents of the agreement which has been amended according to Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. In obtaining the data, juridical legal research methods are used, and through the statute approach and the case approach. Amendments to the contents of the Homologated Peace Agreement are null and void and the process of settlement of payment of accounts receivable is returned to the original homologation decision.